Gender-Based Challenges in Women’s Leadership Careers: A Literature Synthesis - Setyaningrum, Ganis; Juansih (Technium Social Sciences Journal, 2024)
The international community’s initiatives to promote sustainable development, with a particular emphasis on gender equality under SDG 5, have garnered substantial recognition for women leadership. Women who hold leadership positions offer distinctive viewpoints that contribute to workplace positivity, innovation, and decision-making. Nevertheless, they encounter significant obstacles, such as underrepresentation, bias, and restricted opportunities for advancement. This study examines the challenges faced by women in their leadership careers and the influence of organizational practices. This investigation employs a library research methodology to investigate a variety of reference sources, such as books and prior research, in order to establish a theoretical framework regarding women’s leadership. Content analysis is employed to synthesize and interpret pertinent data from sources published within the past decade, thereby guaranteeing the reliability of the information through expert commentary and inter-library checks. The article’s objective is to investigate the internal and external challenges that women encounter in their pursuit of professional advancement, as well as the impact of organizational biases and stereotypes on their leadership roles. It suggests that these factors create barriers and imply implications for increasing the number of women leaders by reviewing literature on management and career studies. The results indicate that women’s career advancement is substantially hindered by gender biases, stereotypes, and structural obstacles. Women’s leadership aspirations are impeded by societal and organizational expectations, despite the progress made in gender equality. The study underscores the necessity of comprehensive strategies to eliminate these biases and foster inclusive leadership environments.